APLIKASI PENDUKUNG KEPUTUSAN PEMILIHAN LULUSAN MADRASAH TSANAWIYAH TERBAIK MENGGUNAKAN METODE SAW - Muhamad Kosasih; Eni Irfiani (Jurnal Informatika, 2019)
Education is a very important aspect of the life of the nation and state especially in helping the progress of the nation and state. Education is also one of the benchmarks in assessing the level of development of the country and improving welfare and improving people's lives. Madrasah Tsanawiyah (MTs) is a formal education school at the level of junior high schools where the management is carried out by the Ministry of Religion. Madrasah Tsanawiyah Al Muawanah is one of the schools that has the goal of producing quality graduates, the problem faced is the difficulty in determining who will be chosen as the best graduate because of the many students who excel and fierce competition between students with subjective nature. To overcome these problems, a decision support system application was designed for the selection of the best graduates using the Simple Additive Weighting (SAW) Method, where this method is often also known as the weighted sum method. The basic concept of SAW is to find a weighted sum of performance ratings for each alternative on all attributes. The criteria used include the average value of the National Standard Madrasah Final Examination, the average value of the National Standard School Examination, the average value of the National Examination, and the average value of report cards. The results of this application can facilitate the school in determining the best graduates based on predetermined criteria. Keywords: Application, Decision Support System, SAW, Best Graduates.